Improving the quality of surveillance colonoscopy in inflammatory bowel disease. (December 2019) - Iacucci, Marietta; Cannatelli, Rosanna; Tontini, Gian Eugenio; Panaccione, Remo; Danese, Silvio; Fiorino, Gionata; Matsumoto, Takayuki; Kochhar, Gursimran S; Shen, Bo; Kiesslich, Ralf; Ghosh, Subrata
Summary: Several recommendations have addressed the topic of improving the quality of surveillance colonoscopy in inflammatory bowel disease. However, there is variation between these recommendations, in part due to the absence of well-defined quality indicators, suggesting that these quality indicators should be studied and developed. We did a systematic review of evidence related to surveillance colonoscopy in inflammatory bowel disease to look at the different variables in this practice and offer a critique of the quality control measures before, during, and after the procedure. We identified several key quality measures that could be adopted in clinical practice, including control of inflammation, optimal bowel preparation, ideal time allocation, training, sedation, detection and characterisation of lesions, therapeutic management of the lesions, and colonoscopic reports. However, further primary research and consensus reports are needed to continue developing roadmaps at a global level.